The effects of climate change on the natural rate of interest: A critical survey - Francesco Paolo Mongelli; Wolfgang Pointner; Jan-Willem van den End (European Central Bank (ECB), 2022)
This survey reviews the literature about the impact of climate change on the natural rate of interest (r*), an important yardstick for monetary policy. Economic and financial developments can lower r* in scenarios with increasing climate-related damages and uncertainty that reduce productivity growth and raise precautionary savings. Instead, in scenarios that assume innovations and investments induced by transition policies, r* could be affected positively. Orderly climate policies have a pivotal role by facilitating the transition to a carbon-neutral economy and supporting a steady investment flow. We discuss the main models used to simulate the effects of climate change on r* and summarize the outcomes. The downward effects of climate change on r* can be substantial, even taking into account the high degree of uncertainty about the outcomes. Moreover, the downward pressure on r* will further challenge monetary policy in the long run, by limiting its policy space
Keywords: E52; Q54; 330; interest rate; monetary policy; climate change; natural rate of interest; social cost of carbon